2016
DOI: 10.1080/15592294.2016.1163460
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma phagocytophilumincreases the levels of histone modifying enzymes to inhibit cell apoptosis and facilitate pathogen infection in the tick vectorIxodes scapularis

Abstract: Epigenetic mechanisms have not been characterized in ticks despite their importance as vectors of human and animal diseases worldwide. The objective of this study was to characterize the histones and histone modifying enzymes (HMEs) of the tick vector Ixodes scapularis and their role during Anaplasma phagocytophilum infection. We first identified 5 histones and 34 HMEs in I. scapularis in comparison with similar proteins in model organisms. Then, we used transcriptomic and proteomic data to analyze the mRNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 99 publications
5
68
0
1
Order By: Relevance
“…The transcriptomics and proteomics data used in this study was previously validated by real-time RT-PCR and Western blot or immunofluorescence for selected genes and proteins, respectively [12, 43]. Nevertheless, 5 selected genes coding for hemoglobin digesting enzymes differentially regulated in response to A. phagocytophilum infection were used for analysis by real-time RT-PCR in individual tick midguts and salivary glands (see Additional file 2: Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptomics and proteomics data used in this study was previously validated by real-time RT-PCR and Western blot or immunofluorescence for selected genes and proteins, respectively [12, 43]. Nevertheless, 5 selected genes coding for hemoglobin digesting enzymes differentially regulated in response to A. phagocytophilum infection were used for analysis by real-time RT-PCR in individual tick midguts and salivary glands (see Additional file 2: Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…How A. phagocytophilum modify tick proteolytic pathways is not known, but may include the regulation of gene expression through epigenetic mechanisms recently shown to be affected by pathogen infection in I. scapularis [43]. These epigenetic mechanisms are probably controlled by secreted bacterial effectors [5558].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggested that a compensatory mechanism might exist by which A. phagocytophilum differentially manipulates tick HMEs to regulate transcription and apoptosis in a tissue-specific manner to facilitate infection but preserving tick fitness to guarantee survival of both pathogens and ticks (Cabezas-Cruz et al, 2016). As previously discussed (Cabezas-Cruz et al, 2016), the mechanisms by which A. phagocytophilum affects tick cell epigenetics is unknown but effector proteins such as AnkA, secreted through T4SS or other secretion mechanisms probably control it (Garcia-Garcia et al, 2009a,b; Rennoll-Bankert et al, 2015). It has been previously demonstrated that A. phagocytophilum AnkA recruits host histone deacetylase 1 (HDAC1) and modifies neutrophils gene expression (Garcia-Garcia et al, 2009a,b; Rennoll-Bankert et al, 2015).…”
Section: Biological Processes Involved In Tick-pathogen Interactionsmentioning
confidence: 95%
“…Recently, A. phagocytophilum was shown to manipulate tick cell epigenetics to increase the levels of the histone modifying enzymes (HMEs), histone acetyltransferases (HATs; 300/CBP), and histone deacetylases (HDACs and Sirtuins) resulting in the inhibition of cell apoptosis to facilitate pathogen infection and multiplication (Cabezas-Cruz et al, 2016). The results of this study suggested that a compensatory mechanism might exist by which A. phagocytophilum differentially manipulates tick HMEs to regulate transcription and apoptosis in a tissue-specific manner to facilitate infection but preserving tick fitness to guarantee survival of both pathogens and ticks (Cabezas-Cruz et al, 2016). As previously discussed (Cabezas-Cruz et al, 2016), the mechanisms by which A. phagocytophilum affects tick cell epigenetics is unknown but effector proteins such as AnkA, secreted through T4SS or other secretion mechanisms probably control it (Garcia-Garcia et al, 2009a,b; Rennoll-Bankert et al, 2015).…”
Section: Biological Processes Involved In Tick-pathogen Interactionsmentioning
confidence: 99%
See 1 more Smart Citation